PEMANFAATAN METODE STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN MEDIA PUZZLE MAKER TERHADAP KEMAMPUAN MENINGKATKAN KAIDAH KEBAHASAAN DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X SMAS KEMALA BHAYANGKARI - Dheni Harmaen; Nadira Fika Anjani; Aries Setia Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to determine the effectiveness of applying the student teams achievement division method assisted by puzzle maker media on the ability to improve linguistic rules in learning to write expository texts in class X SMAS Kemala Bhayangkari Bandung for the 2023/2024 academic year. This research uses a descriptive quantitative method with a research design using a true experimental pretest-posttest control group design. The sample in this research was class X 3 students at SMAS Kemala Bhayangkari for the 2023/2024 academic year. The data collection technique is the N-Gain test to determine the use of methods and media. Based on the research results, it can be concluded that learning using the student teams achievement divisions method assisted by puzzle maker media on the ability to improve linguistic rules in learning to write expository texts for class X SMAS Kemala Bhayangkari students in the 2023/2024 academic year is effective. This is proven by the calculation results using the N-Gain test which is 74.3680 or 74%, which is included in the quite effective category with a minimum N-Gain score of 00% and a maximum of 100%. And the minimum pretest score is 26, the maximum pretest score is 80 and the minimum posttest score is 73 and the maximum score is 100.